Pengaruh Efikasi Diri dan Disiplin Belajar terhadap Hasil Belajar Mata Pelajaran Agama Buddha di SD Swasta Maitreyawira Se-Sumatra - Tommy Tommy (Institut Nalanda, 2024)
This research aims to investigate the influence of learning outcomes with the variable Self-efficacy andThe discipline of learning both individually and together. The research was carried out on 137 class VI elementary school students from which a sample of 102 students was taken on Class VI learning outcomes on academic scores for Buddhist subjects at Maitreyawira Private Elementary Schools in Sumatra. The research uses quantitative research methods. Data analysis uses simple partial correlation and regression, multiple correlation. The conclusion from the results of this research is that there is a positive and very significant influence between the Self-Efficacy variable on Student Learning Outcomes with a significant level of self-efficacy obtained 0.000 < 0.05 and tcount 14,026 > ttable 1,663 the conclusion is that there is an influential, tcount = 14.026 and tcount (0,025;99) = 1.98 score ttable (0,01;99) = 2.36. This means tcount > ttable. There is a positive and very significant influence between the Learning Discipline variable on student learning outcomes with the Learning Discipline significance level obtained 0.000 < 0.05 and tcount 23,775 > ttable 1,663 the conclusion is that there is an influential, tcount = 6.661, and ttable (0,025;99) = 1.98 score ttable (0,01;99) = 2.36. This means tcount > ttable. There is a positive and very significant influence between the self-efficacy and Learning Discipline variables together with the Student Learning Outcomes variable by obtaining a tested hypothesis equation score with the condition Fcount > Ftable. From the calculation results, and score is obtained Fcount = 11,675 and score on Ftable (0,05;100) = 3.09 score Ftable (0,01;100) = 4,82.